Perubahan Sosial Ekonomi Penduduk Lansia Terhadap Kemiskinan di Indonesia - Yofhi Septian Panglipurningrum; Andri Octaviani (Indonesia Economic Journal, 2026)
The increasing number of elderly people is a consequence of demographic transition characterized by rising life expectancy and declining fertility rates. This phenomenon creates various development challenges, particularly elderly poverty, which is influenced not only by economic factors but also by education, health, and living standard dimensions. This study aims to analyze the socio-economic factors affecting elderly poverty in Indonesia and examine changes in elderly poverty conditions during the period 2015–2025. This research employs a quantitative approach using secondary data obtained from the National Socio-Economic Survey (SUSENAS) from 2015 to 2025. Data were analyzed using descriptive statistics and multiple linear regression to determine the effects of education, health, living standards, gender, and residential area on elderly poverty. The results indicate that education, health, living standards, gender, and residential area simultaneously influence elderly poverty. Partially, education, health, and living standards have a negative and significant effect on elderly poverty, while gender does not show a significant effect. Living standards emerge as the most dominant factor influencing elderly poverty. Furthermore, elderly individuals residing in rural areas are more vulnerable to poverty than those living in urban areas. These findings suggest that elderly poverty is a multidimensional issue requiring integrated policy interventions through improved access to education, healthcare services, social protection programs, and enhanced quality of life for older populations.